Growth and Production of Mung Beans in Ultisols with Liquid Brown Algae Compost Applications on Various Combinations of N and K - Johannes Simbolon; Alida Lubis; Jamilah Jamilah (Jurnal Agroekoteknologi, 2019)
The addition of organic matter to the soil and inorganic fertilizer uses can improve soil properties. This objective of the research was to know the effect of liquid brown algae (Sargassum polycystum C.A Argadh.) compost application that combined with N and K fertilizer on chemical properties of Ultisols and growth and production of mung bean. This research was conducted in screen house and laboratory that was using a non-factorial randomized block design with 19 treatments and 2 replications. Data were analyzed with Analysis of Variance (ANOVA) and continues with Duncan’s Multiple Range Test (DMRT) at the level of 1% and 5% and Contrast Test at 5% level. The results of the research showed that the application of liquid compost of brown algae can increase soil pH (H2O) and soil available-P, but decrease soil organic-C, soil total-N, and soil exchange-K. The application of liquid compost of brown algae with various combinations of N and K fertilizers is tendency to decrease all plant parameters such as plant height, number of leaves, number of primary branches, number of pods per plant, and seed weight per plant compared without the treatment of brown algae compost.Keywords: brown algae, mung beans, ultisols